PENGARUH KONSENTRASI RAGI DAN KOMBINASI BIJI LAMTORO GUNG (Leucaena leucocephhala (Lamk.) De Wit) DENGAN KACANG GUDE (Cajanus cajan (L.) Millsp.) TERHADAP KADAR PROTEIN DAN SERAT TEMPE SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) PADA PEMBELAJARAN BIOTEKNOLOGI KONVENSIONAL SMA KELAS XII - Lilik Noviawati; Imam Mahadi; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to determine the effect of yeast concentration and combination of lamtoro gung (Leucaena leucocephala (Lamk.) De Wit) seeds with gude beans (Cajanus cajan (L.) Millsp.) On protein content and tempe fiber as a design of the Student Worksheet (LKPD) in conventional Biotechnology coventioanl material in Class XII High School in April-November 2019. This research was carried out in 2 stages: the experimental stage: the effect of yeast concentration and the combination of lamtoro gung seeds with gude beans on protein content and tempe fiber and LKPD design stage: analysis development of biotechnology teaching materials for grade XII high school. The study used an experimental method by conducting experiments in the Laboratory of the Faculty of Fisheries and Marine Sciences (Faperika), Pekanbaru. Sampling was carried out with a Factorial Complete Randomized Design (CRD) consisting of 2 factors and 3 replications. The parameters in this study are protein content and fiber content. Based on the results of the analysis of variance (Anava) at 5% level, the addition of yeast concentration and the combination of lamtoro gung seeds with peanuts showed a significant effect on tempe characteristics. The addition of 1.5% yeast concentration and the combination of lamtoro gung seeds with gude nuts (25g: 75g) gave an increase in the best quality of tempe and based on the analysis of the potential of research results it can be used as a design of Student Worksheet (LKPD) of biotechnology coventional material of senior high school grade XII.Key Words: Gung lamtoro seeds, Gude Beans, LKPD, Yeast, Tempe